Existence Of Man’s Being And Thinking In Conditions Of Extraordinary Loneliness - Сідоркіна, О. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. For an individual who finds himself in a situation of isolation, a period of self-reflection of consciousness begins with attempts to comprehend the deepest foundations of being, to understand the causes of suffering and find ways to overcome loneliness. A wide research field of the problem of loneliness and its overcoming is given to us by the literary tradition of Robinsonade, where we deal with the existential problems of being that a person faces in these circumstances and how to overcome them. The aim and tasks. The aim of the article is to disclose the features of the manifestation of being, the personality’s thinking and subjective perception in extreme situations of isolation of the perceiving subject, presented in the literary tradition of Robinsonade using two works by famous authors as examples: The Adventures of Robinson Crusoe by D. Defoe and The Mysterious Island by J. Verne. Research methods. The methodological basis of the study is the basic tenets of the philosophy of existentialism, in particular, ideas about the cognitive capabilities of a person in extreme situations, as well as the ideas of philosophical anthropology and social philosophy, which reflect modern views on the communicative processes of the individual, the dialectics of the social and individual at the level of an individual individual. Research results. In the philosophical analysis of the existential foundations of human being and thinking in the extreme conditions of a Robinsonade, we took into account the circumstances and motivation of a person falling into conditions of prolonged isolation, the nature of his socio-communicative connections to forced loneliness, as well as ways of the individual's relationship and communication with the Absolute. The analysis of the plot canvas of the works of “Robinson's” themes testifies a peculiar anthropological experiment to test the physical and moral forces of a person, as well as to a certain existential model of person’s being and thinking. The existential thinking model of Robinson Defoe is characterized by the depth of experiencing his position, guilt and its consequences for the individual, dualistic thinking with a combination of fear of the unknown and a deep desire for survival. In the Robinsonade version of the heroes of the novel by J. Verne, we observe a rationalized and scientientized model of thinking and being with the absence of complex existential self-reflection. Discussion. In the behavior model of Robinson D. Defoe, the idea of guilt is clearly carried out, a painful awareness of its consequences for the person, which leads to the activation of religious consciousness, the need for repentance and the development of active communication in the plan of "I-Supernatural." Staying on the island by the characters of the novel by J. Vern was regarded as a continuation of social activity, service to progressive social ideals, for the victory of which they risked their own lives. Conclusion. The experience of a Robinsonade is a peculiar variant of a person’s deep self-reflection in relation to his position and reasons, as a result of which we can talk about a certain existential model of individual being and thinking, since such a model ultimately determines the features and orientation of person’s subject-practical activity.